Application of the Storytelling Method in the Introduction of the Hadith "Don't Be Angry" in Early Childhood - Rahmi Asmanidar; Muthmainnah Ismail; Heliati Fajriah; Muhammad Faisal (Journal of English Language and Education, 2026)
Previous studies have shown that storytelling is effective for moral and religious learning in early childhood education. However, limited research has examined its use in introducing Islamic teachings, especially the hadith “laa taghdhab” (“do not be angry”), to improve children’s emotional regulation. Therefore, this study aimed to test the effectiveness of the storytelling method in introducing the hadith “laa taghdhab” for children aged 5–6 years at Mentari Kindergarten, Aceh Jaya. This study used a quantitative pre-experimental one-group pretest–posttest design involving 23 children from Group B. Data were collected through structured observation and analyzed using descriptive statistics and a paired-sample t-test. The results showed that the mean score of emotional regulation increased from 2.43 (pretest) to 2.70 (posttest). The paired-sample t-test indicated a significant difference between pretest and posttest scores (t(22) = 2.313, p = 0.030). These findings suggest that storytelling is an effective method to improve emotional regulation through the contextual introduction of the hadith “laa taghdhab” in early childhood.